Extraction of Tannase by the New Strain of Penicillium - Cruz, Roberta; Fonseca, Julyanna C.; de H. C. Maciel, Marília; de Lima, Juliana S.; Albuquerque Sousa, Minelli; Herculano, Polyanna N.; da Silva, Gladstone A.; Medeiros, Erika V.; Souza-Motta, Cristina; Moreira, Keila A. (Current Biotechnology, 2017)
Backgrond: The aqueous two-phase systems (ATPS) have been used as the first purification step in enzyme industrial isolation. Such systems allow the removal of large amounts and different types of contaminants by a simple and economic unit operation. Objective: The tannase extraction was conducted through ATPS composed of polyethylene glycol (PEG) and sodium citrate salt (PEG/citrate). Method: A factorial design model (24) was used to assess the influence of PEG molar mass (400-8000 g mol−1 - MPEG), PEG concentration (12.5-17.5%, w/w - CPEG), citrate concentration (15-25%, w/w, CCIT) and pH (6.0-8.0) on tannase extraction. Results: The tannase is preferably partitioned at the top phase. The highest purification factor (PF = 18.18) was achieved in ATPS using 25% (w/w) PEG 8000 (g mol−1) and 25% (w/w) CCIT at pH 8.0, in which a yield (Y) of 23.37% was obtained. Furthermore, pH was the independent variable that most significantly influenced the response variables. Tannase showed pH and optimum temperature of 5.0 and 60°C, respectively. It was stable in a very short pH range (3.0-6.0) and unstable in the studied temperature range (25-70°C). The tannase activity was stimulated by Ca2+, Co2+, Fe2+ and Mn2+. Organic solvents also increased enzyme activity, particularly in the following rates: 40% chloroform, 20% and 40%, glycerol and 20% and 40% toluene. Conclusion: The ATPS could be used as the first step in tannase extraction from a crude extract, and as a promising and low cost alternative for partial purification of tannase produced by P. rolfssi URM 6216.
Keywords: purification factor